2006
DOI: 10.1086/499632
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofStaphylococcus aureusNasal Colonization in the United States, 2001–2002

Abstract: Many persons in the United States are colonized with S. aureus; prevalence rates differ demographically. MRSA colonization prevalence, although low nationally in 2001-2002, may vary with demographic and organism characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
431
18
21

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 605 publications
(517 citation statements)
references
References 26 publications
47
431
18
21
Order By: Relevance
“…These results agree with those of studies that found lower frequencies of the genes encoding PVL in MSSA clinical isolates (Kuehnert et al 2006), but contrast with data reported from the Czech Republic, where it was found that the lukS/F-PV, tst and sec genes were more frequent in MSSA isolates and enterotoxins genes sea, seb, sed and eta were most prevalent in MRSA strains (Sila et al 2009). Also, in this study, lukS/F-PV were more frequently observed in SCCmec IVc isolates (94%), but they were not restricted to this cassette type and they were also present in SCCmec types I, IVa and V. Other studies conducted in China (Wu et al 2010) and in USA (Abdel-Haq et al 2009) that have evaluated the epidemiological and molecular features of MRSA and MSSA isolates from children found that the most frequent SCCmec type was IVa and all of these strains carried the lukS/F-PV genes.…”
Section: Discussionsupporting
confidence: 89%
“…These results agree with those of studies that found lower frequencies of the genes encoding PVL in MSSA clinical isolates (Kuehnert et al 2006), but contrast with data reported from the Czech Republic, where it was found that the lukS/F-PV, tst and sec genes were more frequent in MSSA isolates and enterotoxins genes sea, seb, sed and eta were most prevalent in MRSA strains (Sila et al 2009). Also, in this study, lukS/F-PV were more frequently observed in SCCmec IVc isolates (94%), but they were not restricted to this cassette type and they were also present in SCCmec types I, IVa and V. Other studies conducted in China (Wu et al 2010) and in USA (Abdel-Haq et al 2009) that have evaluated the epidemiological and molecular features of MRSA and MSSA isolates from children found that the most frequent SCCmec type was IVa and all of these strains carried the lukS/F-PV genes.…”
Section: Discussionsupporting
confidence: 89%
“…In the Eritrean cohort, we did not find that healthcare exposure was significantly associated with MRSA nasal carriage, a finding that has been widely reported in the previous literature [2,5,17,18] and in the German cohort of the current study. Due to relatively small sample sizes in this prospective study, associations may not have been detected, particularly for MRSA isolates.…”
Section: Proteus Mirabilis 1 -supporting
confidence: 61%
“…In contrast, a relatively high prevalence of MRSA colonization was found (11.6%) for a cohort of healthy children aged ≤14 years in community settings in Taiwan over a 5-year period with increasing tendency, despite an overall decrease in the prevalence of nasal colonization by S. aureus [18]. Kuehnert et al [5] concluded that the S. aureus colonization prevalence in the nares was highest in participants 6-11 years old in the United States, whereas MRSA colonization was associated with age ≥60 years and being female but not with recent health-care exposure. An earlier study by Creech et al [17] in healthy US children stated that 36.4% were colonized with S. aureus, whereas 9.2% were colonized with MRSA, significantly higher than in the German cohort.…”
Section: Proteus Mirabilis 1 -mentioning
confidence: 94%
See 2 more Smart Citations